Adverse conditions in the life of children with developmental retardation - Graminha, Sônia Santa Vitaliano; Martins, Maria Angélica de Oliveira (Medicina (Ribeirao Preto), 1997)
The objective of the present study was to identify the risk factors to which children with delayed development referred to the Center of Applied Psychology of FFCLRP-USP over the last five years had been exposed. The group consisted of 12 boys and 10 girls ranging in age from 1 month to 8 years. The data were extracted from the interviews held with the mothers as the time of child enrollment in the service. The problems reported by de mothers on the occasion of the complaint and the adverse events and circumstances that ocurred in the child’s life were classified according to the Category System elaborated by the authors of the present study. The results showed that, in addition to retardation, the most frequent problems reported on the occasion of the complaint were speech, motor coordination, learning and agitation/restlessness problems. Analysis of the adverse circumstances in the life history of this group of children demonstrated that all of them had been exposed to one or more biological risk conditions, the most frequent being congenital problems, mother’s physical health problems during pregnancy, child’s physical health problems, convulsive seizures, complications of delivery, and hospitalization. Furthermore, 36% of the children had been exposed to environmental risk factors, especially those linked to inadequate attitudes and practices of care and education. On the basis of the results obtained, we discuss the implications of the presence of biological risks as an important condition for access to specialized services on the part of the children and their families.